Evaluation of modified short course chemotherapy in active pulmonary tuberculosis patients with human immunodeficiency virus infection in University College Hospital, Ibadan, Nigeria- a preliminary report (2004)
Over the period, 1st October 1999 to 30th April 2002 a clinical trail of the modified short-course chemotherapy (SCC) in newly diagnosed cases of pulmonary tuberculosis with human immunodeficiency virus (HIV) infection in Ibdan, Nigeria was carried out. The modified SCC used was adopted by World Health Organisation(WHO)/ International Union against Tuberculosis and Lungs Diseases (IUALTD) for developing countries and also by the Nigerian National Tuberculosis and Leprosy Control Programmed (NTLCP). THe regimen used consisted of ethambutol(E), isoniazid (H), rifampicin (R), and pyrazinamide (Z) in the intensive phase of 2 months. The continuation phase was 6 maonths of ethambutol (E) and isonized (H), i.e. 2EHRZ/6EH. Sputum conversion was 90%at the second month of treatment and therwe was no bacteriological relapse after 18 months of follow-up. Side effects were few and consisted mainly of continuation phase. It is concluded that this modified 8- month chemotherapy regimen adopted by NTLCP is efficacious in treatment of smear positive pulmonary tuberculosis (PTB) patients with background HIV infection.